2022
DOI: 10.3389/fpsyt.2022.834438
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation and Incident Dementia in the Oldest-Old—A Competing Risk Analysis

Abstract: PurposeSocial isolation is considered a risk factor for dementia. However, less is known about social isolation and dementia with respect to competing risk of death, particularly in the oldest-old, who are at highest risk for social isolation, dementia and mortality. Therefore, we aimed to examine these associations in a sample of oldest-old individuals.MethodsAnalyses were based on follow-up (FU) 5–9 of the longitudinal German study AgeCoDe/AgeQualiDe. Social isolation was assessed using the short form of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Being socially active and involved in social relationships has been shown to have a positive impact on mental and physical well-being and on increased longevity [ 21 , 22 ]. In contrast, SI negatively impacts both physical (increases the risk of cardiovascular diseases, cognitive decline, morbidity, and mortality, as well as stress) [ [23] , [24] , [25] ] and mental health (depression, anxiety, and insomnia) [ [24] , [25] , [26] , [27] ]. Research has shown that one in every 12 older adults suffers severe consequences from SI in terms of health and quality of life [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being socially active and involved in social relationships has been shown to have a positive impact on mental and physical well-being and on increased longevity [ 21 , 22 ]. In contrast, SI negatively impacts both physical (increases the risk of cardiovascular diseases, cognitive decline, morbidity, and mortality, as well as stress) [ [23] , [24] , [25] ] and mental health (depression, anxiety, and insomnia) [ [24] , [25] , [26] , [27] ]. Research has shown that one in every 12 older adults suffers severe consequences from SI in terms of health and quality of life [ 17 ].…”
Section: Introductionmentioning
confidence: 99%